Magneto-optical painting of heat current - Jian Wang (Nature Portfolio, 2020)
Spin caloritronics offers advantages for the thermal management of spintronic devices. Here, the authors demonstrate that the direction of heat currents generated by spin-caloritronic phenomena can be changed by illuminating magnetic materials with visible light.